Holistic approach of Brain-Mind interaction - Datta, AK; Guha, R (Journal of College of Medical Sciences-Nepal, 2015)
We live in three worlds – worlds 1, 2 and 3 with reciprocal interactions which make us perfect human beings. World 1 is the word of physical objects; it comprises the whole of cosmos of matter and energy enriched with nature’s contribution of flora and fauna, and all artefacts made by mankind in the form of books, machines, tools, arts and music. World 2 deals with the states of consciousness and subjective perceptions at three levels of human brain in succession: (a) outer sense provided by all our sense organs that gives rise to the development of (b) inner sense in the form of our emotions, memories, imagination and planning for the future; (c) finally at the core of world 2 there develops a sense of consciousness for self or ego. World 3 is created by man with the development of language of communication that uniquely relates to man. It is the world which is completely unknown to animals. All our means of communication and intellectual efforts are coded in books, the artistic and technological treasures are stored in the museum, and every artifact coded by man is preserved in the world 3. It is the world of civilization and culture. Education is the means whereby each human being is immersed in the world 3 throughout life, participating in the heritage of mankind and so becoming fully human. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12768 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 43-48